Sesamum indicum (sesame) enhances NK anti-cancer activity, modulates Th1/Th2 balance, and suppresses macrophage inflammatory response - Majdalawieh, Amin (2020)
To evaluate the potential immunomodulatory effects of an aqueous extract of Sesamum indicum seeds with regard to splenocyte proliferation, Th1/Th2 balance, macrophage function, and the cytotoxic activity of natural killer (NK) cells. Methods: Splenocyte proliferation was measured by [3H]- thymidine incorporation. Griess assay was performed to evaluate the production of nitric oxide by macrophages. The levels of cytokines secreted by splenocytes and macrophages were measured by ELISA. JAM assay was performed to examine the cytotoxic activity of NK cells against YAC-1 tumor cells. Results: Sesamum indicum significantly enhanced splenocyte proliferation in a dose-dependent manner. Sesamum indicum also increased and suppressed the secretion of Th1 and Th2 cytokines, respectively, by splenocytes. The secretion of key pro-inflammatory mediators (IL-6, TNFα, and nitric oxide) by primary macrophages was significantly inhibited by Sesamum indicum. Moreover, Sesamum indicum increased the cytotoxic activity of NK cells against YAC-1 tumor cells. Conclusions: Sesamum indicum shows potent immunomodulatory, anti-inflammatory, and anti-cancer effects. Constituents of Sesamum indicum may be used as effective therapeutic agents in regulating immune reactions implicated in various infectious and non- infectious conditions including cancer.